Uji Kesukaan Kue Putu Ayu dengan Substitusi Daun Kelor - Siti Annisa Azky; Setyo Widiarto; Rudhi Achmadi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
This research is motivated by new innovations in putu ayu cake products with moringa leaf substitution. In addition to improving the quality and nutritional value of Putu Ayu cake products with Moringa leaves as ingredients. There are still many moringa leaves that have not been developed into putu ayu cake products. The formulation of the research problem is how the results of the analysis of making putu ayu cake with moringa leaf substitution and what is the level of preference for putu ayu cake with moringa leaf substitution with a percentage of 40%, 50% and 60%. The research method and data collection techniques used in this paper are experimental. Data collection techniques are questionnaires, observation, literature study. The conclusion from this writing is that the quality and level of preference (hedonic) of putu ayu cake with moringa leaf substitution is the most preferred by respondents with sample code C2 (40%), while samples C3 (50%) and samples C4 (60%) are quite liked by respondents.